EXPLORING THE ANATOMY OF THE HEART: A STUDY FOR NURSING EDUCATION - Rakhmonova Mohinur Isroilovna; Rajabova Rohila Bakhshilloevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract The human heart is a vital organ that plays a central role in the circulatory system. Its detailed study is essential for nursing students to understand cardiovascular health and diseases. This paper provides an overview of the heart’s anatomy, emphasizing its structural components and physiological functions. This foundational knowledge is crucial for nursing professionals to provide quality care in clinical settings.